Arterial stiffness alone does not explain arteriovenous fistula outcomes. Issue 1 (January 2018) - McGrogan, Damian G.; Stringer, Stephanie; Cockwell, Paul; Jesky, Mark; Ferro, Charlie; Maxwell, Alexander P.; Inston, Nicholas G.
Introduction: Marked arterial adaptation is critical in permitting and sustaining the increased blood flow within an arteriovenous fistula (AVF). The aim of this investigation was to evaluate markers of arterial disease and their association with the early post-operative AVF outcomes. Methods: We included all patients in whom an AVF had been performed after enrolment to the Renal Impairment In Secondary Care (RIISC) study. Primary AVF failure (PFL) was defined as thrombosis at six-week review. All patients underwent BP Tru and Vicorder pulse wave analysis assessments and also had assays of advanced glycation end-products prior to AVF formation. These were correlated with the short-term AVF outcomes. Results: One hundred and eight AVFs were created in 86 patients. The primary patency (PPT) group were found to have significantly higher body mass index (BMI) (p = 0.01). Intraluminal vein diameter was significantly greater in the PPT group than the PFL group (p≤0.01). Mean augmentation index and augmentation index 75 was significantly higher in the PPT group than the PFL group (p = 0.03 and 0.03, respectively). Aortic pulse wave velocity was slower in the PPT group at 10.2 m/s than the PFL group at 10.8 m/s (p = 0.32). Advanced glycation end-product measurements did not vary significantly between the PPT and PFL groups (p = 0.4). Logistic regression analysis provided a predictive model, which demonstrated a predictive value of 78.1% for AVF patency at 6 weeks. Conclusions: All patients in this end-stage renal disease cohort have significant aortic stiffness. The results for pulse wave velocity were slower in the PPT group suggesting a tendency towards stiffer vessels and PFL.